New Religious Movements, Technology, and Science: The Conceptualization of the E-Meter in Scientology Teachings - Bigliardi, Stefano (Zygon, 2016)
This article is aimed at contributing to the study of the relationship that new religious movements entertain with technology and science. It focuses on an object that is central in Scientology's teachings and practice: the Electropsychometer or E-meter. In interaction with the general public, such as in a 2014 TV Super Bowl advertisement, Scientology seems to claim a unique relationship with science and technology in the form of a “combination” and a “connection” evoked while displaying this very E-meter. Hence, exploring the teachings related to it is relevant in order to understand how such combination or connection is conceptualized.